2017
DOI: 10.1111/all.13339
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab rapidly improves angioedema‐related quality of life in adult patients with chronic spontaneous urticaria: X‐ACT study data

Abstract: BackgroundThe X‐ACT study aimed to examine the effect of omalizumab treatment on quality of life (QoL) in chronic spontaneous urticaria (CSU) patients with angioedema refractory to high doses of H1‐antihistamines.MethodsIn X‐ACT, a phase III, double‐blind, placebo‐controlled study, CSU patients (18‐75 years) with ≥4 angioedema episodes during the 6 months before inclusion were randomized (1:1) to receive omalizumab 300 mg or placebo every 4 weeks for 28 weeks. Angioedema‐related QoL, skin‐related QoL impairmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 32 publications
1
60
1
2
Order By: Relevance
“…Furthermore, presence of angio‐oedema is seen as a significant predictor of impaired quality of life in CSU patients and low response to omalizumab treatment . In our study, almost 30% of the patients reported presence of angio‐oedema, which is a bit less compared to previous studies where almost 40–55% of the patients reported angio‐oedema; however, it was not possible to predict a significant difference in clinical response to omalizumab between patients with or without angio‐oedema. Our results were similar to the post hoc analysis based on the randomized controlled trials .…”
Section: Discussioncontrasting
confidence: 94%
“…Furthermore, presence of angio‐oedema is seen as a significant predictor of impaired quality of life in CSU patients and low response to omalizumab treatment . In our study, almost 30% of the patients reported presence of angio‐oedema, which is a bit less compared to previous studies where almost 40–55% of the patients reported angio‐oedema; however, it was not possible to predict a significant difference in clinical response to omalizumab between patients with or without angio‐oedema. Our results were similar to the post hoc analysis based on the randomized controlled trials .…”
Section: Discussioncontrasting
confidence: 94%
“…The proportion of the patients achieving the MCID of 4 points or more in DLQI‐total score at Week 12 was 74.1–77.1% in previous studies, accordingly 69% of our study group reached the MCID or more at Week 12 (Finlay et al, ). Accordingly with our results, the improvement in DLQI subscales was significantly better compared to placebo group (Finlay et al, ; Staubach et al, ), except for personal relationships subscale was not different from placebo group in one study (Finlay et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…The impact of omalizumab on QoL has been investigated in patients participated to Phase III clinical trials (Finlay et al, ; Maurer et al, ; Staubach et al, ). A mean decrease of 4.49–10.3 points in DLQI‐total has been reported at Week 12 (Finlay et al, ; Maurer, Sofen, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Biological therapies have entered the market for patients with asthma almost 15 years ago with anti‐IgE as first‐line therapy for patients with severe allergic asthma and urticaria . Recently, other monoclonal antibodies targeting type 2 inflammation have been approved and are available now for patients with eosinophilic asthma, atopic dermatitis, and urticaria . A number of trials have been done with biological therapies for CRSwNP .…”
Section: Introductionmentioning
confidence: 99%